Valuing spectrum at mm wavelengths for cellular networks - B. A. Shaw; H. F. Beltrán; K. W. Sowerby (International Telecommunications Society (ITS), 2017)
This paper investigates the economic value of spectrum at mm wavelengths. The analysis uses four techniques to value spectrum, namely a benchmarking comparison, a discounted cash flow analysis, a real options approach and a deprival method. The methods to calculate spectrum value presented in this paper can be used for any spectrum band and in any country. However, to determine the value of mm wavelengths for cellular networks, we have used data from New Zealand, specifically for the existing 700 MHz LTE network and for a hypothetical 28 GHz LTE network. These models are based on geographic data, population, cellular traffic analysis and LTE network design from this country. The results from the modelling analysis show that the value of spectrum in this case is bounded by the low value presented by the deprival valuation method and by the high value presented in the real options approach. All results show that as the demand for network capacity increases then mm wavelength spectrum becomes more valuable. This work will be useful to both regulators and operators. To regulators it offers insights into the economic value of mm wavelength spectrum which helps sets fees for spectrum licenses and to set reserve price and expected budgets for future spectrum auctions. To operators this paper offers insights into spectrum valuation techniques and presents data on the value of mm wavelengths for cellular networks.
Keywords: 330